Recovery and research: presentation of the project Intercomunicare - Macedo, Ermelinda (2018)
Projeto: Doenda Mental: Intervanção Comunitária no caminho do Recovery (InterCoMuniCaRe) - Norte-01-0145-FEDER-023855